2022
DOI: 10.3389/fmicb.2022.918986
|View full text |Cite
|
Sign up to set email alerts
|

Influence of planting methods and organic amendments on rice yield and bacterial communities in the rhizosphere soil

Abstract: A comprehensive understanding of rice cultivation techniques and organic amendments affecting soil quality, enzyme activities and bacterial community structure is crucial. We investigated two planting methods (direct seeding and transplanting) of paddy rice (Oryza sativa) and organic amendments with rice straw and biochar on crop yield and soil biological and physicochemical properties. Rhizosphere bacterial communities at the maturity stage of rice growth were characterized through high-throughput 16S rRNA se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…As shown in Figure 5, RS amendment also led to improvements in soil microbial community structure relative to the BC and CK. BC provided high levels of C and an environmental niche compatible with the growth of these root-associated microbes, owing to its stable, porous structure [50]. BC can offer a habitat in which microbes can grow while also influencing the structure and diversity of these rhizosphere soil communities [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 5, RS amendment also led to improvements in soil microbial community structure relative to the BC and CK. BC provided high levels of C and an environmental niche compatible with the growth of these root-associated microbes, owing to its stable, porous structure [50]. BC can offer a habitat in which microbes can grow while also influencing the structure and diversity of these rhizosphere soil communities [8].…”
Section: Discussionmentioning
confidence: 99%
“…The relatively high Gemmatimonas abundance may have resulted from the decomposition of straw over time, given that these bacteria can serve as indirect drivers of cellulose degradation [53]. BC application has previously been associated with increases in relative Actinobacteria abundance in rice paddies [50,54], and members of this phylum have been shown to be present in soil rich in organic matter, particularly under slightly alkaline or neutral conditions [55]. Biochar can facilitate soil N immobilization, which can then be slowly released over time as nutrients are absorbed by the roots of rice plants.…”
Section: Discussionmentioning
confidence: 99%
“…Some research studies have shown that Bacteroidetes and Firmicutes can produce hydrolases (including β-1,4-xylosidase and β-glucosidase) to break down plant biomass (Rao et al, 2021 ). Previous reports classified Bacteroidetes and Firmicutes as copiotrophs (Tang et al, 2022 ), which use labile forms of C for growth and metabolism and grow faster in a nutrient-rich environment.…”
Section: Discussionmentioning
confidence: 99%
“…The roots were forcibly shaken with sterile forceps to separate the roots from the soil, and then five soil samples from each plot were mixed together to generate a composite sample. Finally, all of the soil separated from the roots was sieved by using a 2 mm mesh sieve and put into a sterile zip-lock bag [35,36].…”
Section: Soil Samplingmentioning
confidence: 99%
“…The extraction, PCR amplification, and sequencing of the total genomic DNA of the soil samples were completed according to previous protocols [36]. The primer pair 515F (5 -GTGCCAGCMGCCGCGGTAA-3 ) and 806R (5 -GGACTACHVGGGTWTCTAAT-3 ) was used to amplify the soil bacterial 16S rRNA gene in the V4 hypervariable region [38,39].…”
Section: Analysis Of Soil Chemical Properties and Soil Bacterial Dive...mentioning
confidence: 99%